PENGEMBANGAN ENSIKLOPEDIA DIGITAL MATERI INDONESIAKU KAYA HAYATINYA PADA SISWA KELAS V SD - Imel Permata Sari; Hamdan Hamdan; Andri Valen (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Natural and Social Sciences (IPAS) learning in elementary schools requires instructional media that can present learning materials in an engaging, interactive, and easily understandable manner to enhance students' participation and learning outcomes. However, the availability and use of digital learning media that support the characteristics of IPAS instruction remain limited, highlighting the need for innovative learning media that meet students' learning needs. This study aims to develop a valid, practical, and effective Digital Encyclopedia medium for Grade V IPAS instruction at SD Negeri 79 Lubuklinggau. The study employed a Research and Development (R&D) approach using the ADDIE model. The research subjects consisted of expert validators, educators, and Grade V students at SD Negeri 79 Lubuklinggau. Data were collected through observations, interviews, questionnaires, and tests using questionnaire sheets and written test items as research instruments. The results indicated that the developed product achieved a validity score of 0.84, categorized as high. The practicality assessment by educators and students obtained a score of 76.67%, categorized as practical. Furthermore, the effectiveness test yielded an N-Gain score of 0.56, which falls into the moderate category. Based on these findings, the Digital Encyclopedia developed for Grade V IPAS learning at SD Negeri 79 Lubuklinggau is considered valid, practical, and effective, making it suitable for use as a learning medium to support IPAS instruction in elementary schools. ABSTRAK Pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) di sekolah dasar memerlukan media pembelajaran yang mampu menyajikan materi secara menarik, interaktif, dan mudah dipahami untuk meningkatkan keterlibatan serta hasil belajar peserta didik. Namun, penggunaan media pembelajaran digital yang mendukung karakteristik pembelajaran IPAS masih terbatas sehingga diperlukan inovasi media yang sesuai dengan kebutuhan peserta didik. Penelitian ini bertujuan untuk mengembangkan media Ensiklopedia Digital pada pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) kelas V SD Negeri 79 Lubuklinggau yang valid, praktis, dan efektif. Jenis penelitian ini merupakan Research and Development (R&D) dengan menggunakan model ADDIE. Subjek penelitian terdiri atas validator ahli, pendidik, dan siswa kelas V SD Negeri 79 Lubuklinggau. Pengumpulan data dilakukan melalui observasi, wawancara, angket, dan tes dengan menggunakan lembar angket serta soal tertulis sebagai instrumen penelitian. Hasil penelitian menunjukkan bahwa produk yang dikembangkan memperoleh nilai validitas sebesar 0,84 dengan kategori tinggi. Penilaian kepraktisan oleh pendidik dan siswa memperoleh skor 76,67% dengan kategori praktis. Sementara itu, hasil uji keefektifan menunjukkan nilai N-Gain sebesar 0,56 dengan kategori sedang. Berdasarkan hasil tersebut, media Ensiklopedia Digital pada pembelajaran IPAS kelas V SD Negeri 79 Lubuklinggau dinyatakan valid, praktis, dan efektif sehingga layak digunakan sebagai media pembelajaran untuk mendukung proses pembelajaran IPAS di sekolah dasar.